The Role of Socioscientific Issues (SSI) in Natural of Science (NOS) Learning: A Systematic Literature Review - Ayu Mar'ati Barokatun Ni'mah; Muh Syahrul Padli; Roro Risya Iswara; Heru Kuswanto (Postgraduate, University of Mataram, 2025)
This study analyzes the role of socioscientific issues (SSI) in improving learners' competence in learning the nature of science (NOS) based on articles in SCOPUS-indexed journals. This systematic review used the PRISMA framework to classify the pedagogical aspects of SSI in science education. Of the initial 717 articles, 53 were selected based on inclusion and exclusion criteria. Results showed that SSI-based NOS learning can develop competencies such as argumentation, critical thinking, collaboration, communication, and conceptual understanding. Examples of SSI integration include climate change, biotechnology, biodiversity, waste management, and chemical engineering. Its implementation involves inquiry, problem, and model-based strategies, with methods of discussion, debate, digital resources, and role-play. This review concludes that SSI provides a transformational approach to NOS learning by enhancing learners' cognitive and interpersonal competencies, making it a promising framework for future educational practice.